2011
DOI: 10.1007/s00430-011-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Mycobacterium smegmatis to a pathogenic phenotype via passage of epithelial cells during macrophage infection

Abstract: Mycobacteria encounter many different cells during infection within their hosts. Although alveolar epithelial cells play an essential role in host defense as the first cells to be challenged upon contact with mycobacteria, they may contribute to the acquisition of mycobacterial virulence by increasing the expression of virulence or adaptation factors prior to being ingested by macrophages on the side of pathogens. From this aspect, the enhanced virulence of nonpathogenic Mycobacterium smegmatis (MSM) passed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Because of the evidence that mycobacteria become more infective after the first intracellular infection [ 61 , 62 ], we evaluated whether this holds for M. abscessus obtained from macrophages. The aforementioned results showed that M. abscessus were highly internalized by macrophages and ended up in a mature lysosomal compartment without, however, evidence of intracellular death (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the evidence that mycobacteria become more infective after the first intracellular infection [ 61 , 62 ], we evaluated whether this holds for M. abscessus obtained from macrophages. The aforementioned results showed that M. abscessus were highly internalized by macrophages and ended up in a mature lysosomal compartment without, however, evidence of intracellular death (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Although second infection occurred to a lesser degree when compared to initial infection, only the clinical strain CRM0019 grew in A549 cells and macrophages in a second infection, which may explain the long persistence of the observed in vivo infection [ 32 ]. Evidence suggests that intracellular passage through epithelial cells changes the mycobacterial phenotype to a more pathogenic one during infection of macrophages, epithelial or endothelial cells [ 61 , 77 , 78 ]. In our study, mycobacteria obtained from macrophages were not more infective but were still able to survive in either macrophages or alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also was found the rapid stirring on ice in a overhead stirrer to avoid agglutination, followed by passage through a 0.8 μm membrane to guarantee a predominance of bacteria just in controls by Ziehl-Neelsen staining (Shin, Han, Manning, & Collins, 2007). Lastly, there is also gentle sonication over short periods of time, for example, at 30 W for 5 min (Chapeton-Montes, Plaza, Barrero, & Patarroyo, 2007;Kim et al, 2011).…”
Section: Mycobacterium Dissociation and Multiplicity Of Infection-bmentioning
confidence: 99%
“…Epithelium processing and interaction with bovine mammary epithelial cells (MAC-T), a surrogate for the intestinal epithelium, results in enhanced phagocytosis during secondary infection [ 23 ]. Changes to invasion phenotype due to epithelial processing are also seen with M. smegmatis , a saprophytic mycobacteria that is nonpathogenic [ 24 ]. M. smegmatis exposed to A549 epithelial cells had a significant increase in intracellular growth during secondary infection in THP-1 macrophages [ 24 ].…”
Section: Introductionmentioning
confidence: 99%